A COMPARATIVE ANALYSIS OF CONSUMER PREFERENCES BETWEEN ONLINE AND OFFLINE STORE (CASE STUDY ON FASHION PRODUCT) - Dumais, Lady Priscillia; Tumbuan, Willem J.F.A; Tumiwa, Johan R (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Consumers have become a demanding target and an important factor to running fashion business. Fashion is accepted by the consumers and influences their behavior in many ways to buy a new product. Shopping is an activity that certainly done because of need or simply to fulfill a desire. The aim of this research is to analyze consumer preferences between online and offline store in Manado based on price, availability of brand and product, promotional schemes, standardization of product and family or social experience. This research is quantitative type of research, which uses primary data obtained through questionnaires and uses independent sample t-test as the analytical tool. The population of this research is peoples in Manado who has experience shopping in Online and Offline Store, where the sample size is taken from 100 respondents who also has experience with Online and Offline Store. The analysis and discussion from this research found that there is significant difference between online and offline store measured by price and promotional schemes. And there is no significant difference between online and offline store measured by availability of brand and product, standardization of product and family or social experience. Besides all these, there are some recommendations for online and offline store in fashion product that can be used as a reference for the development and deepening of knowledge management marketing, especially consumer preferences.Keywords: online and offline store, consumer preferences, fashion product.